Diversity and Morphological Characterization of Fungi in the Mangrove Forest of Belawan, North Sumatra - Putri Hasanah; Erman Munir; Kiki Nurtjahja (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to isolate and morphologically characterize fungi from the mangrove area of Belawan, North Sumatra, to better understand their diversity and potential roles within the ecosystem. Mangrove forests are vital coastal ecosystems that support diverse microbial communities, including fungi, which play essential roles in nutrient cycling and ecosystem stability. This study aimed to isolate and characterize fungal diversity from the Belawan mangrove area, North Sumatra. Sampling was conducted on water and soil, followed by fungal isolation on Potato Dextrose Agar containing 1% NaCl. A total of 15 fungal isolates were obtained—nine from water and six from soil samples. Morphological characterization revealed considerable diversity in colony shape (circular, irregular, filamentous), texture (granular, cottony, velvety), margin (undulate, filiform, entire), and color (green, white, pink, grayish white, black, dark brown). Microscopic examination showed various conidial morphologies, including round conidia that burst open like fans, crescent-shaped conidia, needle-shaped conidia with branched conidiophores, and conidia arranged in chains on phialides. The dominant genus identified was Aspergillus, exhibiting typical macroscopic and microscopic traits. Physical-chemical parameters of the sampling sites indicated stable environmental conditions suitable for mangrove fungi. This study highlights the rich fungal diversity in the Belawan mangrove ecosystem and underscores the ecological importance of fungi in maintaining mangrove health. The results provide a foundation for further molecular identification and exploration of the biotechnological potential of mangrove-associated fungi.